Vitamin K2 Supplementation Does Not Affect Vitamin K-Dependent Coagulation Factors Activity in Healthy Subjects: A Pilot Study - Tan, Jing (Curr Dev Nutr, 2020)
OBJECTIVES: Vitamin K is generally regarded as a procoagulant drug with physicians, concerns have been raised about its effects on hemostasis in the healthy population. We aimed to investigate whether vitamin K2 affects activities of individual vitamin K dependent coagulation factors in healthy individuals without anticoagulation treatment. METHODS: Forty healthy volunteers between 25 and 40 years old were recruited. They received 90 μg of vitamin K2 every day for 30 days. Prothrombin time (PT), activated partial thromboplastin time (APTT), thrombin time (TT), international normalized ratio (INR), fibrinogen (FIB) levels and blood coagulation factors II, VII, IX, and X activity levels (F II : C, FⅦ : C, FⅨ : C,FⅩ : C), protein induced by vitamin K absence or antagonist-II (PIVKA-II), which is uncarboxylated prothrombin were measured at day 0, and day 30 after vitamin K2 administration. Plasma diluted 1:10 from vitamin K2 group and healthy control group were assayed for the activity of factors II, VII, IX, and X. RESULTS: PT, APTT, TT, and FIB did not show significant difference at day 30 when compared with baseline. The activities of coagulation factors II, VII, IX, and X was not significantly different with baseline (97.28 ± 12.42% vs. 99.96 ± 10.24%, P = 0.24 for F II: C; 76.12 ± 15.82% vs. 76.40 ± 12.33%, P = 0.92 for FⅦ: C; 97.65 ± 13.98% vs. 99.65 ± 13.30%, P = 0.47 for FⅨ: C; 89.18 ± 10.76% vs. 92.01 ± 10.46%, P = 0.1 for FⅩ: C) . PIVKA-II levels were not changed with 30 days vitamin K2 supplementation (21.62 ± 3.21 vs. 23.87 ± 2.65 mAU/ml, P = 0.16). After 30 days vitamin K2 administration, factor II, Ⅶ, Ⅸ, and Ⅹ activity of plasma diluted up to 10 times were proportionally decreased, and did not show significant difference with the healthy control without vitamin K2 exposure (10.32 ± 1.24% vs. 10.97 ± 1.55%, P = 0.38 for F II: C; 9.52 ± 2.94% vs. 9.14 ± 1.79%, P = 0.68 for FⅦ: C; 11.78 ± 2.12% vs.11.65 ± 1.54%, P = 0.87 for FⅨ: C; 8.22 ± 1.28% vs. 8.92 ± 1.13%, P = 0.21 for FⅩ: C). CONCLUSIONS: Vitamin K2 supplementation at recommended dosage does not affect vitamin K-dependent coagulation factors activity in healthy subjects. Uncarboxylated prothrombin (PIVKA-II) in healthy individuals is not decreased with vitamin K supplementation. FUNDING SOURCES: None.